Sparse Random Linear Network Coding With Precoded Band Codes - Li, Ye; Zhu, Jun; Bao, Zhihua (IEEE communications letters, 2017)
This letter proposes a sparse network code based on band matrices for lossy networks. The proposed code is precoded, has no wrap-around, and allows only a limited number of bands. Compared with existing works, the code simplifies decoding, enables more flexible recoding, and is able to significantly reduce the reception overhead that might be caused by recoding.